Platelet-Rich Plasma for the Treatment of Knee Osteoarthritis: A Review - Piuzzi, Nicolas S.; Chughtai, Morad; Khlopas, Anton; Harwin, Steven F.; Miniaci, Anthony; Mont, Michael A.; Muschler, George F. (The Journal of Knee Surgery, 2017)
Platelet-rich plasma (PRP) consists of a volume of plasma with a platelet concentration above whole blood baseline values. Based on the group of bioactive molecules that platelets release when activated and the regenerative and healing potential they have, the use of PRP has followed a rapid development and application in orthopedics, with applications that frequently outpaces the basic science and clinical evidence supporting its use. Currently, significant heterogeneity and discrepancies exist between the different types of available PRP formulations. Because of this, although there is a vast literature on PRP, the published results are often contradictory, making it challenging to obtain definitive conclusions. Therefore, the purpose of this review article is to provide an overview of PRP with a focus on (1) preparation protocols; (2) nomenclature and classifications; (3) biological effects; and (4) clinical evidence of its role in the treatment of knee osteoarthritis. On the basis of the current evidence, although PRP injections reduced pain and improved function more efficiently when compared with controls, these findings need to be interpreted with caution due to the limited level of evidence and high risk of bias. There is a need for a standardized scientific approach for analyzing PRP formulations composition, beginning with standardization of PRP preparation protocols, and detailed characterization of the final product (e.g., platelets and leukocytes content, volume, growth factors profile). Good quality and sizeable double-blinded randomized trials will be required to establish whether or not PRP injections are effective and should be included as a standard of care for the management of patients with knee osteoarthritis.
Keywords: osteoarthritis; knee; platelet-rich plasma; intra-articular injections; PRP